Frontiers and New Trends in the Science of Fermented Food and Beverages - Lidia Solís-Oviedo, Rosa; de la Cruz Pech-Canul, Ángel (IntechOpen, 2019)
From time immemorial fermented foods have undoubtedly contributed to the progress of modern societies. Historically, ferments have been present in virtually all human cultures worldwide, and nowadays natives from many ancient cultures still conduct a wide variety of food fermentations using deep-rooted recipes and processes. Within the last four centuries, scientific research has started to unravel many aspects of the biological process behind fermentations, which has contributed to the improvement of many industrial processes. During our journey in the research field, we have always been attracted to the development of scientific research around fermentations, especially autochthonous ferments: a natural repository of novel biomolecules and biological processes that will positively impact on many application fields from health, to food, to materials.